Empathetic Storytelling, Volume II : Sparking Transformation in Education - Murawska, Jaclyn; Nank, Sean (Critical Storytelling, 2024)
In the Critical Storytelling series, this latest book elevates the voices of a myriad of authors, using empathetic storytelling to spark transformation in education. Stories connect us through the meaning we make, intricately woven in a diverse tapestry of shared experiences held together with the delicate thread of our humanity. Uncovering implicit biases and choices inherent in the two themes of belonging and identity, and caring and relationships, the editors offer concrete strategies for classroom teachers, professors, educational leaders, and policy makers to use storytelling to complement awareness and discourse with calls to action. Contributors are: Noor Ali, Eisa Al-Shamma, Carol Battle, Anne René Elsbree, Ana M. Hernández, Mark Hevert, Edward D. Kim, Viviane King-Adas, Amanda Moody Maestranzi, Lily Mittnight, Jaclyn Murawska, Sean Nank, Jackie Palmquist, Michael Palmquist, MJ Palmquist, Rania Saeb, Karen Toralba, Suzanne M. Van Steenbergen and Sarah Catherine Vaughan.